1934
DOI: 10.1085/jgp.17.6.727
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Electrolytes

Abstract: It would be natural to suppose that potassium enters Valonia as KC1 since it appears in this form in the sap. We find, however, that on this basis we cannot predict the behavior of potassium in any respect. But we can readily do so if we assume that it penetrates chieflyl.2 as KOH. We may then say that under normal conditions potassium enters the cell because the ionic activity product (K) (OH) is greater outside than inside. This hypothesis leads to the following predictions:1. When the product (K) (OH) becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1934
1934
1976
1976

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But if any hydrolysis of KNO a does occur, a fall in the pH value of the solution should increase the formation of HNO a , owing to an increase in 6.5 This attempt to explain the way in which NO a or NH 4 may be absorbed in excess of oppositely charged salt ions is similar to the hypothesis of Osterhout and his coworkers that potassium enters Valonia chiefly as KOH, the rate of entrance depending on the difference between the ionic activity product [K+] X [OH-j outside and inside the plant (Jacques and Osterhout, 1934). It appears that the principles outlined above may furnish an explanation of the reaction changes shown in figures 1-3.…”
Section: Influence Of the Ratio Of No A To Nh4mentioning
confidence: 83%
“…But if any hydrolysis of KNO a does occur, a fall in the pH value of the solution should increase the formation of HNO a , owing to an increase in 6.5 This attempt to explain the way in which NO a or NH 4 may be absorbed in excess of oppositely charged salt ions is similar to the hypothesis of Osterhout and his coworkers that potassium enters Valonia chiefly as KOH, the rate of entrance depending on the difference between the ionic activity product [K+] X [OH-j outside and inside the plant (Jacques and Osterhout, 1934). It appears that the principles outlined above may furnish an explanation of the reaction changes shown in figures 1-3.…”
Section: Influence Of the Ratio Of No A To Nh4mentioning
confidence: 83%
“…With regard to the metabolized anions, NO3-, SO4 =, and phosphate, there are only a few studies in vacuolated algae which deal with the transport of these ions. Jacques and Osterhout (21) found that NO3-was concentrated in the sap ofValonia macryophysa by 2,000-fold and in the sap of H. osterhoutii by 500-fold over the concentration in natural seawater, which is less than 10 /xM. The accumulation of phosphate and SO4 = has been shown in several species of marine algae (23,24,35).…”
Section: Steady-state Ionic Distributionmentioning
confidence: 98%